ANALISIS KONSEP DASAR BIMBINGAN KONSELING DI SD ISLAM COKROAMINOTO 01 KALABAHI - Maria Bainhana; Inang Naila Mustapa, Lambertus Lupuikoni, Loni Sarlota Mau Klaping, Yessy Mata, Petrus Mau Tellu Don (CV. ADIBA AISHA AMIRA, 2025)
This journal aims to describe the basic concepts and implementation of guidance and counseling at SD Islam Cokroaminoto 01 Kalabahi. The issues addressed include students' emotional and behavioral problems caused by family conditions such as broken homes, lack of focus in learning, and difficulties in social interaction. This research employs a qualitative method with a descriptive approach through interviews and direct observation of the homeroom teacher. The findings show that teachers use emotional, social, and psychological approaches, and involve parents and families in addressing students’ problems. In addition, teachers apply specific methods such as ADHD (Attention Deficit Hyperactivity Disorder) strategies and ISP (Individualized Service Plan) for students with special needs. Counseling activities are conducted informally to ensure students feel comfortable and their privacy is respected. These findings indicate that guidance and counseling services play a crucial role in supporting students’ personal and social development, and in creating a positive learning environment in elementary schools.